Entre morosidade e eficiência: estudo sobre justiça e serviço público judiciário no estado brasileiro - Moreira Neto, Francisco das Chagas (2023)
Using the Brazilian Judiciary as the object of study, the question is posed: "how and to what extent do the notions of public service, institutions, slowness, efficiency, and access to justice relate in the context of the crisis of the Brazilian Judiciary?". Through bibliographic and documentary research, with a deductive approach and descriptive-explanatory bias, a critical study of these important categories of Brazilian public law was carried out. The general objective aims to provide an initial overview of justice and judicial public service in Brazil, investigating categories often related to the scenario of the Brazilian Judiciary crisis. Specific objectives include the construction of the notion of judicial public service; the investigation of the historical-constitutional path in the formation of the institutional identity of the Brazilian Judiciary; the distinction and analysis of the concepts of access to justice and access to the Judiciary; the critical examination of the institutions that make up the essential functions of justice, building the legal-instrumental sense of the power to litigate in the current constitutional paradigm; the analysis of the political and legal circumstances surrounding the reforms of the general public administration and the Judiciary, highlighting the conditions that underlie the crisis narratives, their perspectives, and possible consequences. Therefore, in three chapters, the analysis of the concept of public service and its relationship with the Brazilian Judiciary is carried out, including the historiography of the constitutions and the institutional identity of the Judiciary (chapter 1); the study of the instruments of the Brazilian justice system, the differentiation between access to justice and access to the Judiciary, and the analysis of the power to litigate and litigation in the current legal context (chapter 2); finally, the investigation of reforms in public administration and the implementation of a managerialist structure, analyzing efficiency in the Judiciary and the implications of crises arising from slowness (chapter 3). As a result of the study, the importance of addressing the complexity of the Brazilian judicial public service in a multidisciplinary and joint manner involving various actors and sectors of society was highlighted; it is necessary to foster a culture of integrity and ethics among justice system professionals, adopting a single inter-institutional agenda focused on justice. Through these efforts, the Judiciary can strengthen itself and contribute to the consolidation of democracy and the construction of a more just and inclusive society.